Penerapan Pendekatan Saintifik Dalam Pembelajaran IPAS Materi Perubahan Dan Pelestarian Lingkungan Pada Siswa Kelas V SD - Nuralia Radiani Rustan; Herlina; Ma’ruf (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
This study aims to describe the application of a scientific approach in science learning and analyze its influence on students' understanding and attitudes towards the material of environmental change and conservation. The scientific approach, which includes observing, asking, trying, reasoning, and communicating, is applied to increase students' active involvement and encourage deeper conceptual understanding. The research method used is descriptive qualitative with fifth-grade students in an elementary school in Makassar City as the subjects. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that the application of a scientific approach can increase students' interest in learning, critical thinking skills, and concern for environmental issues. Thus, the scientific approach is proven effective in creating meaningful and contextual science learning.a.